2019
DOI: 10.1097/wco.0000000000000687
|View full text |Cite
|
Sign up to set email alerts
|

Advance in genetics of migraine

Abstract: Purpose of review Migraine is a primary headache disorder and one of the most common and disabling neurological diseases worldwide. Genome-wide association studies have identified ≈40 genetic loci associated with migraine. How these and other genetic findings are used to expand our knowledge on the pathophysiological mechanism of common migraine and rare migraine variants will be discussed. Recent findings The genetic load, based on common polygenic variation, is higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 40 publications
2
65
1
1
Order By: Relevance
“…Moreover, migraine is a polygenic disease with the contribution of multiple genetic variants, each of them having a relatively small effect. It is believed that migraine development is a result of the complex interaction of numerous gene variants and epigenetic mechanisms with both environmental and lifestyle factors [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, migraine is a polygenic disease with the contribution of multiple genetic variants, each of them having a relatively small effect. It is believed that migraine development is a result of the complex interaction of numerous gene variants and epigenetic mechanisms with both environmental and lifestyle factors [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of VM are considered sporadic, but familial aggregation of VM with autosomal-dominant inheritance has been described in several families, supporting a genetic background for the condition (3,4). Genome-wide association studies (GWASs) have identified numerous single-nucleotide polymorphisms (SNPs) associated with a genetic predisposition for migraine with or without aura (5,6). Familial hemiplegic migraine (FHM), which is a subtype of migraine with aura, is caused by mutations in CACNA1A, ATP1A2, and SCN1A (7).…”
Section: Introductionmentioning
confidence: 99%
“…Migraine is caused by mutations in the CACNA1A (Calcium voltage-gated channel subunit alpha1 A), ATP1A2 (ATPase Na+/K+ transporting subunit alpha 2) and SCN1A (Sodium voltage-gated channel alpha subunit 1) genes. 6 The CACNA1A gene sends signals for making one part (the alpha-1 subunit) of a calcium channel called CaV2.1. This subunit forms the pore through which calcium ions can flow.…”
Section: Introductionmentioning
confidence: 99%